1990
DOI: 10.1016/0042-6989(90)90096-4
|View full text |Cite
|
Sign up to set email alerts
|

The intraocular straylight function in 129 healthy volunteers; Dependence on angle, age and pigmentation

Abstract: The direct compensation method allows for an accurate (standard deviation below 0.05 log unit) determination of intraocular light scattering between 3.5 and 25 deg of scattering angle and is suitable for untrained subjects. The method was used to study population behaviour and individual variation in 129 volunteers between 20 and 82 yr of age, visual acuity equal to or better than one and no apparent eye pathology. The results indicate straylight to increase with the 4th power of age, doubling at 70. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
124
1
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(134 citation statements)
references
References 9 publications
8
124
1
1
Order By: Relevance
“…The discomfort usually reported by some patients during light therapy appears to be due to glare, which is caused, in part, by intraocular light scatter that can reduce contrast and result in blurring of the retinal image (Ijspeert et al 1990). Wavelength may or may not affect glare (Boettner andWolter 1962 andWooten andGeri 1987), but lower illuminances of light do serve to reduce intraocular light scatter.…”
Section: Discussionmentioning
confidence: 99%
“…The discomfort usually reported by some patients during light therapy appears to be due to glare, which is caused, in part, by intraocular light scatter that can reduce contrast and result in blurring of the retinal image (Ijspeert et al 1990). Wavelength may or may not affect glare (Boettner andWolter 1962 andWooten andGeri 1987), but lower illuminances of light do serve to reduce intraocular light scatter.…”
Section: Discussionmentioning
confidence: 99%
“…As the eye ages, aberrations and scattering are increased (Ijspeert et al, 1990;Siik et al, 1992;Whitaker et al, 1993;van den Berg, 1995;Hennelly et al, 1998;Guirao et al, 1999;Calver et al, 1999;Kuroda et al, 2002;Fujikado et al, 2004), thus resulting in LSF broadening. In this study, since primarily the central region of the double-pass LSF was examined, aberrations and diffraction likely had a dominant role in determining the LSF shape.…”
Section: Discussionmentioning
confidence: 99%
“…This location from one side of the peak occurred at a distance of (48±11) arc min (mean±SD, N=21). Therefore, the central part of the double-pass LSF, which was governed primarily by aberrations and diffraction, was taken into account (Ijspeert et al, 1990;Beckman et al, 1994;van den Berg, 1995;Westheimer and Liang, 1995).…”
Section: Section Image Processing and Analysismentioning
confidence: 99%
“…Two main reasons were identified: part of the light projected on to the retina is not absorbed but is reflected back into the eye by the layers of the fundus, 1 and the fact taht the eye wall, including the iris, is not optically opaque. 2 Both effects depend on the amount of pigmentation in the fundus and the eye wall respectively. The light originating from fundus reflectance and eye wall translucency does not partake in proper image formation on the retina, but is scattered in the eye to create a veil of light over the retinal image.…”
Section: Introductionmentioning
confidence: 99%
“…Blue-eyed caucasians were found to have higher retinal straylight values compared to pigmented brown-eyed non-caucasians, leading to the conclusion that pigmentation is a source of variation in straylight in normal eyes. 2,3 Van den Berg et al 4 showed that this pigmentation dependence is partly caused by variations in transmission of light through the ocular wall. For dark-brown eyes of pigmented individuals transmission was found to be two orders of magnitude lower than for blue-eyed individuals.…”
Section: Introductionmentioning
confidence: 99%